Orang Lom: Masalah Sosial dan Ancaman Kearifan Lokal dalam Tinjauan Sosiologi - Jamilah Cholillah (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2015)
Social issues and local wisdom of Orang Lom People in Air Abik a contrasting duality. On the one side local knowledge continue to be maintained and preserved even exploited for the benefit of generations, but on the other side, the local wisdom, leaving only sadness being trapped on social issues such as local institutional stagnation and conflict prolonged tenure. The contrasting sides led to the existence of indigenous communities Lom People weakened and started moving towards industrialization resulted in waning social memory and the passage of the process of social exclusion.